Ecology - Bowman, William D (Sinauer Associates, Inc., 2018)
"Ecology is at the heart of understanding our world-- it serves as the glue that brings together information from a multitude of very different scientific disciplines, and it integrates this information in a way that informs us about how nature works. As our environment continues to change at an alarming rate it becomes increasingly critical that we improve our understanding of the repercussions of climate change, non-sustainable extraction of resources, the spread of invasive species, and pollution. Stewardship of resources that humanity requires-- food, clean water, clean air, and many others-- is best understood through the lens of ecological understanding."--Préface.